Underspecification and monophthongization in the first and second possessive markers in Chachapoyas Quechua - Valqui, Jairo (2017)
This paper discusses on the emergence of long and short monophthongized vowels in a number of suffixes of the Quechua variety spoken in Chachapoyas. In particular, vowel monophthongization occurs within the possessive suffixes that mark first and second person in this Quechua variety. Previous studies have explained that alternations between [i]/[i:] and [e]/[e:] are the result of variations in the quality of the initial segment /-y/ that appears in both first and second person possessive suffixes. Similarly, previous research has described the alternation between short and long vowel segments (i.e. [i]/[i:] and [e]/[e:]) as the outcome of stress variation. However, recent acoustic evidence suggests that the initial segment of both possessive suffixes is not /-y/ but a subespecified coronal segment. Moreover, this evidence allows to explain the alternation between short and long vowels as caused by the lexical phonology of Chachapoyas Quechua rather than as a result of stress variation. After discussing these new findings, this paper provides some insights about the linguistic change of the first person possessive suffix in other Quechua varieties.